AmeliCA: A community-driven sustainable framework for Open Knowledge in Latin America and the Global South - Becerril García, Arianna (2018)
The Latin American region has an ecosystem where the nature of publication is conceived as the act of making public, of sharing and not as the publishing industry. Scholarly institutions and universities composed an informal and non-explicit cooperative that finances journals with its own faculty members and publish them in Open Access, which means that everybody gets benefit from everybody else?s investment. Nevertheless, Latin American Open Access ecosystem is facing a fragmentation. One can identify at least two main approaches: one determined by the so called ?mainstream science? through the indexation in WoS or Scopus as the only-way to validate research; and a second approach that recognizes institutional and regional quality research, that strengthens publishers inside universities by empowering editors with technology and training and that claims for a more responsible research assessment, with custom strategies but with the capacity to interact in a global scale. This work shows AmeliCA, a concrete initiative that emerged as a result of the convergence of various stakeholders that shares the second approach.AmeliCA is a configuration of strategies, in response to the international, regional, national and institutional contexts, that seeks a cooperative, sustainable, protected and non-commercial Open Access solution for Latin America that can be extended to the Global South.